1995
DOI: 10.1177/000331979504600708
|View full text |Cite
|
Sign up to set email alerts
|

Results of Transcutaneous Electrical Stimulation (TES) in Cure of Lower Extremity Arterial Disease

Abstract: The results of the treatment of 24 subjects--10 of them diabetic--with peripheral obstructive arterial disease of the lower limbs by transcutaneous electrical stimulation (TES) have been studied. The chronic ischemia of the lower extremities was complicated with ulceration in 12 and initial or advanced gangrene in 6 patients. All patients had been treated with antiplatelet drugs, pentoxifylline, and vasodilating drugs for many years. The drug therapy was continued, and TES was given daily for twenty minutes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…Unlike the energies just mentioned, ES for wound healing is not a new intervention, as positive clinical research outcomes began appearing in the literature more than 40 years ago. 23 With steady advances in ES technologies, combined with a plethora of compelling clinical research [11][12][13][14][15][16][17][18][19][20][21][23][24][25][26][27][28][29][33][34][35][36][37] and the strong pressure ulcer treatment guideline recommendations of the European Pressure Ulcer Advisory Panel and National Pressure Ulcer Advisory Panel, 44 the Registered Nurse Association of Canada, 45 and the Paralyzed Veterans of America, 46 it seems likely that wound-care practitioners will significantly expand the clinical use of this treatment in chronic wound management. Further strong support for this intervention was presented by Koel 47 in 2009 at the 19th Conference of the European Wound Management Association, where he reported on the preliminary phase of a Cochrane review of the effects of ES on wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the energies just mentioned, ES for wound healing is not a new intervention, as positive clinical research outcomes began appearing in the literature more than 40 years ago. 23 With steady advances in ES technologies, combined with a plethora of compelling clinical research [11][12][13][14][15][16][17][18][19][20][21][23][24][25][26][27][28][29][33][34][35][36][37] and the strong pressure ulcer treatment guideline recommendations of the European Pressure Ulcer Advisory Panel and National Pressure Ulcer Advisory Panel, 44 the Registered Nurse Association of Canada, 45 and the Paralyzed Veterans of America, 46 it seems likely that wound-care practitioners will significantly expand the clinical use of this treatment in chronic wound management. Further strong support for this intervention was presented by Koel 47 in 2009 at the 19th Conference of the European Wound Management Association, where he reported on the preliminary phase of a Cochrane review of the effects of ES on wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetric biphasic waveforms may be electrically balanced or unbalanced. The use of biphasic symmetrical (charge balanced) 33 ( Fig. 2C) and asymmetrical (charge unbalanced) 13,14 (Fig.…”
Section: Pulsed Currentmentioning
confidence: 99%
“…Thus, the size of the wound may not have provided sensitivity to demonstrate the actual changes. The macroscopic analysis to verify the effect of the TENS on wound healing has already demonstrated satisfactory results in diabetic wounds (6,15), leprosy wounds (16), pressure ulcers (17,18), burn injuries (10) and chronic venous ulcers (19 -21), which are wounds that have total areas greater than 8mm.…”
Section: Discussionmentioning
confidence: 99%
“…The existing scientific basis regarding the use of TENS in wound healing is more evident for chronic wounds initiated or aggravated by diseases such as diabetes (15), leprosy (16), peripheral arterial insufficiency (6,22), chronic venous insufficiency (19 -21) and in pressure ulcers in patients with spinal cord injuries (17,18). Considering acute wounds, animal studies have demonstrated that low-frequency TENS optimized the healing of burn lesions in elderly rats (10), improved healing by increasing growth factors in the dermis and epidermis (13) and reduced proinflammatory cytokines in the dermis by inhibiting the inflammatory phase, promoting a decrease in the duration of the cicatrization process (23).…”
Section: Introductionmentioning
confidence: 99%
“…[80][81][82][83][84][85] Two of the original clinical reports are often identified as controlled studies since they included a relatively large number of subjects; however, they compared healing outcomes produced after EST to only six patients with bilateral wounds. 86,87 Goldman et al 58,79,88,89 have produced a number of very compelling reports where EST was used to treat patients with ischemic wounds of the leg and foot often complicated by diabetes.…”
mentioning
confidence: 99%